The Concept Of Sertu According To Madhhab Syafi'I Its Importance In The Industrial Sector And Its Implementation Challenges In Brunei Darussalam - Cecep Soleh Kurniawan; Hjh Mas Nooraini Hj Mohiddin; Mohd Mahyeddin Mohd Salleh; Ahmad Rafiki (Halal Center of UIN Sunan Ampel Surabaya, 2026)
Non-Indexed Publication